The landscape of research on ferroptosis under hypoxic conditions: a bibliometric analysis - Yu, Di; Hu, Yibo; Ma, Meijuan; Li, Wenjia; Zhao, Xiaohui (Frontiers in pharmacology, 2025)
Ferroptosis is a newly identified type of iron-dependent cell death that characterized by an increase in intracellular iron ions, which disrupt the balance of the cellular lipid peroxidation system, causing lipid peroxidation and ultimately resulting in cell death. Interestingly, ferroptosis is modulated by hypoxia and plays a role in hypoxia-related diseases. Therefore, we performed a bibliometric review of the Web of Science Core Collection (WoSCC) database to investigate the link between ferroptosis and hypoxia from January 2013 to December 2023. The core collection within the Web of Science bibliographic index was consulted to extract relevant articles and reviews. Data on publications, countries, institutions, authors, journals, citations, and keywords in the included studies were systematically analyzed using Microsoft Excel 2019 and CiteSpace 6.3.R1 software. A comprehensive analysis and visualization of 472 research papers on ferroptosis under hypoxic conditions published between 2013 and 2023 revealed emerging research hotspots and trends. Initially, a scarcity of studies existed in this field. However, this was succeeded by a significant increase in research interest in subsequent years, culminating in a peak of 204 publications in 2023. Research in this field focused primarily on the Asian region. Notably, research hotspots include diseases related to hypoxia, treatment therapy and pathogenesis. Among the researchers in this field, Supuran emerged as the most prolific author. Wuhan University was the leading institution in terms of research output, and China was the most prolific country in this area of study. Among the top ten journals ranked by the number of publications, nine were classified as Q1, indicating the high level of credibility of these studies. The research conducted by Stockwell et al., featured in the journal " ," currently has the most citations. Present scholarly pursuits are primarily focused on comprehending the mechanisms through which interventions affect hypoxia-related diseases through the ferroptosis pathway, as well as on probing and pinpointing prospective treatment targets. This study highlights key areas of interest and emerging trends in ferroptosis research in the presence of hypoxic conditions, thus providing valuable insights for future directions of exploration for the diagnosis and treatment of hypoxia-related diseases.